2014
DOI: 10.1016/j.jmoldx.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Identification of miRNAs for Classification of Tumor Origin

Abstract: Carcinomas of unknown primary origin constitute 3% to 5% of all newly diagnosed metastatic cancers, with the primary source difficult to classify with current histological methods. Effective cancer treatment depends on early and accurate identification of the tumor; patients with metastases of unknown origin have poor prognosis and short survival. Because miRNA expression is highly tissue specific, the miRNA profile of a metastasis may be used to identify its origin. We therefore evaluated the potential of miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 44 publications
5
50
0
1
Order By: Relevance
“…The highly tissue specific origin of miRNAs leads to an efficient identification of metastatic cancers of unknown primary origin. Søkilde et al [23] reported in a series of 208 tumors, representing 15 different histologies including PCa, that miRNA expression profiling on paraffin tissue can efficiently predict the primary origin of the tumor. The authors developed a new miRNAs classification algorithm, obtaining an overall accuracy of 85% (CI: 79%-89%).…”
Section: Mirnas and Cancermentioning
confidence: 99%
“…The highly tissue specific origin of miRNAs leads to an efficient identification of metastatic cancers of unknown primary origin. Søkilde et al [23] reported in a series of 208 tumors, representing 15 different histologies including PCa, that miRNA expression profiling on paraffin tissue can efficiently predict the primary origin of the tumor. The authors developed a new miRNAs classification algorithm, obtaining an overall accuracy of 85% (CI: 79%-89%).…”
Section: Mirnas and Cancermentioning
confidence: 99%
“…However, the molecular mechanisms involved in the initiation and progression of HCC are still poorly understood. Recently, the role of epigenetic regulation, particularly DNA methylation and the aberrant expression of miRNAs, in the occurrence and development of cancers is gradually being recognized (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Due to their specific expression in different organisms, tissues and cells, miRNAs may provide potential novel biomarkers [27-29]. Our previous study indicated that different T. gondii genotypes have their unique miRNA profiles [30].…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are also important for pathogen-host interactions [23-26]. Recently studies have indicated that miRNAs may represent potential biomarkers for various biomedical problems, such as the differentiation of different tumors and muscular tissues [27-29], and they may provide biomarkers for the characterization of different genotypes of Toxoplasma gondii [30]. …”
Section: Introductionmentioning
confidence: 99%